2019
DOI: 10.1016/j.visres.2018.10.006
|View full text |Cite|
|
Sign up to set email alerts
|

Psychophysical evaluation of individual low-level feature influences on visual attention

Abstract: In this study we provide the analysis of eye movement behavior elicited by low-level feature distinctiveness with a dataset of synthetically-generated image patterns. Design of visual stimuli was inspired by the ones used in previous psychophysical experiments, namely in free-viewing and visual searching tasks, to provide a total of 15 types of stimuli, divided according to the task and feature to be analyzed. Our interest is to analyze the influences of low-level feature contrast between a salient region and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 162 publications
(199 reference statements)
0
22
0
Order By: Relevance
“…Metrics used in saliency benchmarks [40] consider all fixations during viewing time with same 275 importance, making saliency hypotheses unclear of which computational procedures perform best using real image 276 datasets. Previous psychophysical studies [16,17] revealed that fixations guided by bottom-up attention are influenced 277 by the type of features that appear in the scene and their relative feature contrast. From these properties, the order of 278 fixations and the type of task can drive specific eye movement patterns and center biases, relevant in this case.…”
Section: Model Evaluation 273mentioning
confidence: 99%
See 4 more Smart Citations
“…Metrics used in saliency benchmarks [40] consider all fixations during viewing time with same 275 importance, making saliency hypotheses unclear of which computational procedures perform best using real image 276 datasets. Previous psychophysical studies [16,17] revealed that fixations guided by bottom-up attention are influenced 277 by the type of features that appear in the scene and their relative feature contrast. From these properties, the order of 278 fixations and the type of task can drive specific eye movement patterns and center biases, relevant in this case.…”
Section: Model Evaluation 273mentioning
confidence: 99%
“…Later studies 15 considered that maximizing information of scenes was the key factor on forming visual feature representations. To test 16 that, Bruce & Tsotsos [10] implemented a saliency model (AIM) by extracting sparse representations of image statistics 17 (using independent component analysis). These representations were found to be remarkably similar to cells in V1, 18 which follow similar spatial properties to Gabor filters [11].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations